The Influence of Pregnancy Class Education on the Prevention of Pregnancy Complications - Evita Widyawati; Poppy Farasari; Oktaviana Manda Putri; Friska Oktaviana (STIKes Budi Luhur Cimahi, 2026)
The Maternal Mortality Rate (MMR) remains a significant public health problem in Indonesia, largely due to delays in recognizing danger signs during pregnancy and seeking medical care. Pregnant women need to be aware of the importance of receiving regular antenatal care from healthcare professionals and participating in pregnancy classes. This study used a quasi-experimental design with a one-group pretest–posttest approach to determine the effect of pregnancy class education on the prevention of pregnancy complications at the Kauman Community Health Center, Tulungagung Regency, from February to March 2026. A sample of 25 third-trimester pregnant women was selected through purposive sampling, and data were collected using validated questionnaires. The results showed a substantial improvement in the respondents' abilities. Before the intervention, 64% (n = 16) of the participants were unable to detect early pregnancy complications; after the intervention, this proportion decreased to 36% (n = 9), while 64% (n = 16) were able to detect complications. Data analysis using a paired-samples t-test showed a significant improvement in the ability to detect pregnancy complications, with a mean difference of 0.280, t(24) = 3.055, and p = 0.005. These findings demonstrate that structured pregnancy class education effectively empowers pregnant women to identify early risk factors and provides an important strategy for community health centers to reduce maternal and neonatal morbidity through community-based preventive education.